Unwilling or unable? Using three-dimensional tracking to evaluate dogs' reactions to differing human intentions - Völter, Christoph J.; Lonardo, Lucrezia; Steinmann, Maud G. G. M.; Ramos, Carolina Frizzo; Gerwisch, Karoline; Schranz, Monique-Theres; Dobernig, Iris; Huber, Ludwig (Proceedings of the Royal Society. B, Biological sciences, 2023)
The extent to which dogs ( Canis familiaris ) as a domesticated species understand human intentions is still a matter of debate. The unwilling–unable paradigm has been developed to examine whether nonhuman animals are sensitive to intentions underlying human actions. In this paradigm, subjects tended to wait longer in the testing area when presented with a human that appeared willing but unable to transfer food to them compared to an unwilling (teasing) human. In the present study, we conducted the unwilling–unable paradigm with dogs using a detailed behavioural analysis based on machine-learning driven three-dimensional tracking. Throughout two preregistered experiments, we found evidence, in line with our prediction, that dogs reacted more impatiently to actions signalling unwillingness to transfer food rather than inability. These differences were consistent through two different samples of pet dogs (total n = 96) and they were evident also in the machine-learning generated three-dimensional tracking data. Our results therefore provide robust evidence that dogs distinguish between similar actions (leading to the same outcome) associated with different intentions. However, their reactions did not lead to any measurable preference for one experimenter over the other in a subsequent transfer phase. We discuss different cognitive mechanisms that might underlie dogs’ performance in this paradigm.